Caesarean section in a semi-rural hospital in Northern Namibia - Petrova Vera; Meguid Tarek; van Dillen Jeroen; van Roosmalen Jos (BMC, 2007)
Abstract Background Increasing caesarean sections rates (CSR) are a major public health concern and the prevention of the first caesarean section, which often leads to repeat operations, is an important issue. Analyzing caesarean sections can help to identify factors associated with variations in CSR and help to assess the quality of clinical care. Methods In a retrospective observational study, during a two year period, indications of 576 caesarean sections were analyzed using intra-operative internal pelvimetry and a record keeping system in a semi-rural hospital in Northern Namibia. Results Most caesarean sections were done for dystocia (34%) followed by repeat caesarean section (31%). The true conjugate (distance between the promontorium to mid pubic bone) was significantly smaller in these recurrent indication groups when compared to non recurrent indications. Conclusion In this rural hospital the introduction of Delee Pelvimetry and a caesarean section record keeping system was found to be a simple and cheap method to analyse indications for caesarean sections, which may help in reducing unnecessary caesarean sections.